Outcomes of patients supported by mechanical ventilation and their families two months after discharge from pediatric intensive care unit - MacDonald, Simon; Du Pont-Thibodeau, Geneviève; Thibault, Celine; Jutras, Camille; Roumeliotis, Nadia; Farrell, Catherine; Ducharme-Crevier, Laurence (Frontiers in Pediatrics, 2024)
The outcomes of children undergoing mechanical ventilation (MV) in a Pediatric Intensive Care Unit (PICU) remain poorly characterized and increasing knowledge in this area may lead to strategies that improve care. In this study, we reported the outcomes of children receiving invasive mechanical ventilation (IMV) and/or non-invasive ventilation (NIV), 2 months after PICU discharge.Methods: This is a post-hoc analysis of a single-center prospective study of PICU children followed at the PICU follow-up clinic at CHU Sainte-Justine. Eligible children were admitted to the PICU with ≥2 days of IMV or ≥4 days of NIV. Two months after PICU discharge, patients and families were evaluated by physicians and filled out questionnaires assessing Quality of life (Pediatric Quality of Life Inventory TM, ), development milestones (Ages and Stages Questionnaire), and parental anxiety and depression (Hospital Anxiety and Depression Scale). Results: One hundred and fifty patients were included from October 2018 to December 2021; 106 patients received IMV (±NIV), and 44 patients received NIV exclusively.Admission diagnoses differed between groups, with 30.2% of patients in the IMV group admitted for a respiratory illness vs. 79.5% in the NIV group. For the entire cohort, QoL scores were 78.1% for the physical domain and 80.1% for the psychological domain, and were similar between groups. Children with a respiratory illness exhibited similar symptoms at follow-up whether they were supported by IMV vs. NIV. For developmental outcomes, only 22.2% of pre-school children had normal scores in all ASQ domains. In the entire cohort, symptoms of anxiety were reported in 29.9% and depression in 24.6 of patients% Conclusions: PICU survivors undergoing mechanical ventilation, and their families, experienced significant morbidities 2 months after their critical illness, whether they received IMV or NIV. Children with respiratory illness exhibited a higher prevalence of persistent respiratory difficulties post PICU, whether they underwent IMV or NIV.Patients' quality of life and parental symptoms of anxiety and depression did not differ according to the type of respiratory support. These findings justify the inclusion of patients receiving NIV in the PICU in follow-up assessments as well as those receiving IMV.